PENERAPAN METODE JARIMATIKA UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI PERKALIAN DI KELAS II SD NEGERI 27 TALANG KELAPA - Desanjaya, Jossy; Lusiana, Lusiana; Suriadi, Aan (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This research is motivated by the difficulty of elementary school students in understanding the concept of mathematical multiplication, which is often considered abstract and can cause learning boredom. The low initial learning outcomes indicate the need for a more concrete and interactive learning method. Therefore, this study focuses on testing and describing the improvement in student learning outcomes after the jarimatika method is applied. The main objective is to determine the effectiveness of this method on multiplication material in grade II of SD Negeri 27 Talang Kelapa. This study used a pre-experimental design with a one-group pre-test-post-test design on 25 students. The important stages of the study include giving a pre-test to measure initial abilities, applying the jarimatika method as a treatment, and giving a post-test to measure the final results. The collected learning outcome data were analyzed using descriptive statistics and the N-Gain test. The results showed a significant increase in student learning outcomes. The average score of students increased from 42.40 in the pre-test to 74.60 in the post-test. Further analysis using N-Gain resulted in an average score of 0.56, indicating a level of improvement in the